2019
DOI: 10.3390/foods8070243
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Responses to Basic Tastes for Sensory Evaluation of Chocolate Using Biometric Techniques

Abstract: Facial expressions are in reaction to basic tastes by the response to receptor stimulation. The objective of this study was to assess the autonomic nervous system responses to basic tastes in chocolates and to identify relationships between conscious and unconscious responses from participants. Panelists (n = 45) tasted five chocolates with either salt, citric acid, sugar, or monosodium glutamate, which generated four distinctive basic tastes plus bitter, using dark chocolate. An integrated camera system, coup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 73 publications
3
35
2
Order By: Relevance
“…The use of analogous stimuli should be taken into account for future work as it might help CNNs detect facial expressions more clearly. Gunaratne et al [24] reported expressions of sadness positively associated with the tasting of salty chocolate. This may provide a hint to find out why the proposed FER system yielded a classification of sadness so often.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of analogous stimuli should be taken into account for future work as it might help CNNs detect facial expressions more clearly. Gunaratne et al [24] reported expressions of sadness positively associated with the tasting of salty chocolate. This may provide a hint to find out why the proposed FER system yielded a classification of sadness so often.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to FER, novel types of analyses including recording of emotions and physiological changes elicited in consumers when trying new food products have contributed to achieving a more complete understanding of consumer responses [24].…”
Section: Introductionmentioning
confidence: 99%
“…It is helpful to use a second type of measurement to provide further evidence. Nowadays, there is a growing interest in applying biometric measurements such as eye tracking, electroencephalography (EEG), and facial recognition in sensory and consumer studies, therefore, adding an objective complement to measures of sensory perception [39,[48][49][50][51][52][53][54][55][56]. Among these biometric instruments, EEG is a common non-invasive neuroimaging technique that records electrical activity along the scalp.…”
Section: Objective Biometric Measurement Of Likingmentioning
confidence: 99%
“…More recently, the use of emojis has been implemented for this purpose, as consumers tend to identify emotions using proxy images related to expressed emotions as non-verbal cues, as these are more closely associated with their feelings [ 25 , 26 , 27 ]. Subconscious responses from consumers have also been evaluated for chocolate and beer using computer vision techniques and machine learning to assess their facial expressions [ 15 , 16 , 20 , 28 , 29 ]. These studies may produce more relevant information that may be missed using conventional self-reported sensory analysis, especially for insect-based food products.…”
Section: Introductionmentioning
confidence: 99%